DETERMINANTS OF JOB PERFORMANCE AMONG MALAYSIA’S YOUNG ADULTS IN KLANG VALLEY: FLEXIBLE WORKING ARRANGEMENT, WORK ENGAGEMENT AND EMOTIONAL MOOD - Choo , See Ting (Electronic Journal of Business and Management, 2021)
This research investigates the impact of three key determinants—Flexible Working Arrangement (FWA), Work Engagement, and Emotional Moods—on the job performance of young adults in Klang Valley, Malaysia. Using a quantitative method, data was collected from 170 respondents via online closed-ended questionnaires utilizing a 5-point Likert Scale. The study performed both descriptive and inferential analyses using SPSS. Findings indicate that while FWA has a moderately strong positive relationship with performance, Work Engagement and Emotional Moods exhibit significant and strong positive relationships. Specifically, Emotional Mood explained the highest variation in job performance (62%), followed by Work Engagement (53.7%) and FWA (41.9%). The study concludes that HR policies should prioritize these variables to enhance the productivity of the young workforce.